Correction: Longhitano et al. The Crosstalk between GPR81/IGFBP6 Promotes Breast Cancer Progression by Modulating Lactate Metabolism and Oxidative Stress. Antioxidants 2022, 11, 275 - Lucia Longhitano; Stefano Forte; Laura Orlando; Stephanie Grasso; Alessandro Barbato; Nunzio Vicario; Rosalba Parenti; Paolo Fontana; Angela M. Amorini; Giuseppe Lazzarino; Giovanni Li Volti; Michelino Di Rosa; et al. (Antioxidants, 2025)
In the original publication, there was a mistake in Figure 4C as published [...]